Increasing the Quality of Financial Audit Engagements by Implementing Quality Management Standards - Soare, Janina; Mustățea, Aura Oana (Acta Universitatis Danubius. Œconomica, 2025)
The main goal of this research is to identify solutions for the implementation of the new legislative provisions within audit companies in order to accelerate the process of improving the quality of the audit and implicitly the audited accounting information. The performed evaluations show that the national audit companies have not developed sufficient and adequate financial audit quality control procedures, they have to go through an updating process, following the new vision of the International Auditing and Assurance Standards Board (IAASB) The method of implementing procedures for the transition from quality control to quality management of financial audit engagements is analysed based on the example of an audit company. The main methods employed are: in-depth analyzes of specialized literature containing national and international scientific papers and studies in the field of financial audit, found in national and international publications as well as cross-sectional and longitudinal analysis methods. The conclusion of the study is that a financial audit quality management system is not yet implemented, the current internal regulations are still associated with quality control and not quality management and the audit companies in our country can quickly adapt their procedures for the transition from quality control to quality management of financial audit engagements.